Analytical Solution to a Forced Kawahara Equation - Salas S., Alvaro H. (Research Updates in Mathematics and Computer Science Vol. 4, 2024)
In this paper we introduce a forced Kawahara equation. We solve it making use of a direct ansatz method. We also solve it via splines method. Numerical examples illlustrate the accuracy of the obtained results.